Nasal chondromesenchymal hamartomas in a cohort with pathogenic germline variation in DICER1 - Vasta, Lauren M. (Rhinol Online, 2020)
BACKGROUND: Nasal chondromesenchymal hamartomas are benign, rare nasal tumors associated with DICER1 pathogenic germline variation. They can be locally destructive and recurrent if not completely resected. METHODOLOGY: In this single-center, case-control study, otorhinolaryngology evaluations and review of systems questionnaires of DICER1-carriers and controls enrolled in the DICER1 Natural History Study at the National Cancer Institute were collected. Review of these medical records were analyzed to determine if DICER1-carriers experienced different sinonasal clinical manifestations compared to controls. Additionally, the number of diagnoses of nasal chondromesenchymal hamartoma cases in the NCI DICER1 study was compared against the total person years of observation of DICER1-carriers in the study to determine the total number of cases per person-years of observation. Lastly, both the NCI DICER1 study and the International Pleuropulmonary Blastoma/DICER1 Registry were queried for unpublished cases of nasal chondromesenchymal hamartomas. RESULTS: There were no clinical differences in sinonasal symptomatology between DICER1-carriers and control patients seen in the ENT clinic. We observed of two cases of nasal chondromesenchymal hamartoma in a total of 555 person-years of monitoring DICER1-carriers. We include six unpublished nasal chondromesenchymal hamartoma cases. When combined with a comprehensive literature review, 38% of nasal chondromesenchymal hamartoma cases had at least one additional DICER1-associated tumor and 24% of the NCMH were found in the ethmoid sinus, the most commonly involved paranasal sinus. CONCLUSIONS: We quantify the risk of developing nasal chondromesenchymal hamartomas in our cohort of 236 DICER1-carriers, report six unpublished cases, and provide an updated review of the literature.